2011
DOI: 10.1371/journal.pone.0025729
|View full text |Cite
|
Sign up to set email alerts
|

The Flexible Nature of Unconscious Cognition

Abstract: The cognitive signature of unconscious processes is hotly debated recently. Generally, consciousness is thought to mediate flexible, adaptive and goal-directed behavior, but in the last decade unconscious processing has rapidly gained ground on traditional conscious territory. In this study we demonstrate that the scope and impact of unconscious information on behavior and brain activity can be modulated dynamically on a trial-by-trial basis. Participants performed a Go/No-Go experiment in which an unconscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 52 publications
6
35
0
Order By: Relevance
“…Yet, other studies have shown that unconscious stimuli can trigger cognitive control (Lau & Passingham, 2007), including response inhibition (Hughes, Velmans, & De Fockert, 2009;Lau & Passingham, 2007;Mattler, 2003;van Gaal, Ridderinkhof, Fahrenfort, Scholte, & Lamme, 2008;Wokke, van Gaal, Scholte, Ridderinkhof, & Lamme, 2011) and task set preparation (Lau & Passingham, 2007;Mattler, 2003). Together, these results suggest that perhaps neither awareness nor subjective confidence is critical for response inhibition or task set preparation.…”
Section: Discussionmentioning
confidence: 89%
“…Yet, other studies have shown that unconscious stimuli can trigger cognitive control (Lau & Passingham, 2007), including response inhibition (Hughes, Velmans, & De Fockert, 2009;Lau & Passingham, 2007;Mattler, 2003;van Gaal, Ridderinkhof, Fahrenfort, Scholte, & Lamme, 2008;Wokke, van Gaal, Scholte, Ridderinkhof, & Lamme, 2011) and task set preparation (Lau & Passingham, 2007;Mattler, 2003). Together, these results suggest that perhaps neither awareness nor subjective confidence is critical for response inhibition or task set preparation.…”
Section: Discussionmentioning
confidence: 89%
“…Albeit insufficient to give rise to a conscious sensory experience, such neural impulses may alter behavioural patterns toward more protective activities, such as frequently alternating position and avoiding prolonged positional immobilization. The lack of conscious perception does not exclude the possibility that such non-conscious sensory input nevertheless influences behaviour adaptively (20).…”
Section: Discussionmentioning
confidence: 99%
“…What all these observations have in common is that they show that a process that is meant to be carried out on the basis of conscious stimuli (e.g., a task cue) can also be performed on the basis of unconscious stimuli (e.g., Van Opstal, Gevers, Osman, & Verguts, 2010). Although recent studies have suggested ways to overcome interpretations in term of stimulus-response associations (Wokke, van Gaal, Scholte, Ridderinkhof, & Lamme, 2011), it seemed to be a crucial precondition for cognitive control functions triggered by unconscious external stimuli, that participants are also confronted with conscious instances of the stimuli (e.g., Chiu & Aron, 2014). On the basis of this literature, Kunde, Reuss, and Kiesel (2012) contrasted cognitive control processes that are initiated due to explicit information (like the aforementioned stop signal, task cue, or spatial cue) with cognitive control processes that are initiated due to implicit information (like conflict adaptation, as information has to be integrated to determine conflict in the first place).…”
Section: Discussionmentioning
confidence: 99%